Executive Function evaluation in children with learning disabilities through a tablet assessment battery (2020)
Executive functions are a set of psychological processes that are necessary for the cognitive control of behavior: selecting and successfully monitoring behaviors that facilitate the attainment of certain goals. These skills are necessary to guide learning of new information. Core executive function (CEF) are inhibitory control, working memory and cognitive flexibility. They regulate and control other skills and behaviors, and also have influence on more basic skills such as attention, memory systems, and praxis. Executive functions allow setting goals and carrying them out through planning and monitoring, keeping inhibited thoughts, behaviors and emotions that interfere. This research consists of determining neuropsychological EF profiles in different clinical populations evaluated with tablet-based test. Two batteries developed by CEDETI UC were applied: Yellow Red and TENI (Infant Neuropsychological Assessment Test). The sample consists of 175 argentine children, between 7 and 12 years old, divided in two groups, clinical and control. The obtained scores show the importance of distinguishing profiles between these three CEF within the clinical population comparing with a typical developing group. The overall index obtained differentiates the groups best. Children with dyscalculia, autistic spectrum disorder and borderline intellectual disability obtain significantly lower scores having greater difficulties in EF.